Annual Plan 2004-05 Volume - I Planning and Statistics Department Government of Karnataka - Planning Commission (Planning Commission, 2004)
The outlay for the Annual Plan 2004-05 is Rs 12322 99 crores This represents an increase of26.00% over the ,budgeted outlay of Rs.9779.75 crores in 2003-04 and forms 28% of the Tmenth Plan outlay of Rs.43558.22 crores. The District Plan size for Annual Plan 2004-05 is Rs. 1012.66 crores. The outlay proposed for Externally Aided Projects in Annual Plan 2004-05 is Rs. 1574.75 crores. Under the Special Component Plan Rs.367.00 crores have been earmarked for the welfare of the Scheduled Castes and Rs.93.43 crores for the Scheduled Tribes under the Tribal Sub Plan.
Planning and Statistics Department Government of Karnataka